2020
DOI: 10.30773/pi.2020.0007
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Problematic Smartphone Use, Unhealthy Behaviors, and Mental Health Status in Korean Adolescents: Based on Data from the 13th Korea Youth Risk Behavior Survey (2017)

Abstract: Objective We aimed to assess the associations between problematic smartphone use, unhealthy behaviors, and mental health status among adolescents.Methods The data for this cross-sectional study were obtained from the 13th Korea Youth Risk Behavior Survey (2017). From among the 62,276 adolescents who participated in this nationwide web-based survey, 54,603 (87.7%) who used smartphones were selected as the study population. Unhealthy behaviors included smoking, drinking, physical inactivity, skipping breakfast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
2
20
0
1
Order By: Relevance
“…The risk of suicidal ideation, suicide planning, and suicide attempt was higher among those with inadequate sleep, smokers, alcohol users, drug users, and those with smartphone overdependence. These are similar to the ndings of previous Korea-based studies, where the risks of suicidal ideation, suicide planning, and suicide attempt were found to be higher among female students than male students [32][33][34]. A possible reason for this is that male students tend to interpret an event cognitively, while female students are more heavily in uenced by and sensitive to the emotional aspects of the event [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…The risk of suicidal ideation, suicide planning, and suicide attempt was higher among those with inadequate sleep, smokers, alcohol users, drug users, and those with smartphone overdependence. These are similar to the ndings of previous Korea-based studies, where the risks of suicidal ideation, suicide planning, and suicide attempt were found to be higher among female students than male students [32][33][34]. A possible reason for this is that male students tend to interpret an event cognitively, while female students are more heavily in uenced by and sensitive to the emotional aspects of the event [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that different types of stressful life events have different effects on mental health problems. For example, some studies have found that interpersonal stress and academic stress are associated with depressive symptoms, sleep quality, suicidal ideation, and PSU (81)(82)(83); another study showed that punishment significantly predicted depressive symptoms, but have no effects on poor sleep quality and suicidal ideation (84). Future research should examine the effects of specific types of stressful life events on different mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence from one study ( n = 54,603, some concerns) that using a smartphone for social media and chatting compared with education purposes affects stress 43 …”
Section: Resultsmentioning
confidence: 99%